INDUKSI TUNAS GADUNG (Diocorea hispida Dennst) SECARA IN VITRO - ARIF, NORMA; ANSI, AZHAR; WIJAYANTO, TEGUH (Jurnal Agroteknos, 2014)
Yam (Dioscorea hispida Dennst) is a tuber crop that belonges to food sources and has not been widely recognized by the public. Aside from being a food ingredient, it can also be used as a natural pesticide. Until now, efforts to use the potential of yam have not been handled well. This research was conducted at the In vitro Laboratory of the Faculty of agriculture, Haluoleo University, from May to July 2014. The purpose of the study was to obtain the proper concentration of BAP to induce yam plant shoots in vitro. The research design used was a completely randomized design with 5 replications. One segment of the stem explants were grown on MS basic medium with different concentrations of BAP (0.5-4 ppm), with 5 replications and each replication consisted of 1 bottle containing 2 explants. Data were analyzed using Duncan's Multiple Range Test (DMRT). The research results showed that the addition of various concentrations of BAP affected the span of the emergence of the first shoots but did not affect the percentage of explants alive and growing shoots. BAP concentration of 2 mg / L was the optimal concentration to induce shoots of yam (Dioscorea hispida) with a span began to shoot appearance at week 4 after planting.